How does obstructive sleep apnoea evolve in syndromic craniosynostosis? A prospective cohort study. Issue 7 (23rd May 2013) - Driessen, Caroline; Joosten, Koen F M; Bannink, Natalja; Bredero-Boelhouwer, Hansje H; Hoeve, Hans L J; Wolvius, Eppo B; Rizopoulos, Dimitris; Mathijssen, Irene M J
Abstract : Objective: To describe the course of obstructive sleep apnoea syndrome (OSAS) in children with syndromic craniosynostosis. Design: Prospective cohort study. Setting: Dutch Craniofacial Centre from January 2007 to January 2012. Patients: A total of 97 children with syndromic craniosynostosis underwent level III sleep study. Patients generally undergo cranial vault remodelling during their first year of life, but OSAS treatment only on indication. Main outcome measures: Obstructive apnoea-hypopnoea index, the central apnoea index and haemoglobin oxygenation-desaturation index derived from consecutive sleep studies. Results: The overall prevalence of OSAS in syndromic craniosynostosis was 68% as defined by level III sleep study. Twenty-three patients were treated for OSAS. Longitudinal profiles were computed for 80 untreated patients using 241 sleep studies. A mixed effects model showed higher values for the patients with midface hypoplasia as compared to those without midface hypoplasia (Omnibus likelihood ratio test=7.9). In paired measurements, the obstructive apnoea-hypopnoea index (Z=−3.4) significantly decreased over time, especially in the first years of life (Z=−3.3), but not in patients with midface hypoplasia (Z=−1.5). No patient developed severe OSAS during follow-up if it was not yet diagnosed during the first sleep study. Conclusions: OSAS is highly prevalent in syndromic craniosynostosis. There is some natural improvement, mainly during the first 3 years of life and least in children with Apert or Crouzon/Pfeiffer syndrome. In the absence of other co-morbid risk factors, it is highly unlikely that if severe OSAS is not present early in life it will develop during childhood. Ongoing clinical surveillance is of great importance and continuous monitoring for the development of other co-morbid risk factors for OSAS should be warranted.